2022
DOI: 10.3389/fphys.2022.841278
|View full text |Cite
|
Sign up to set email alerts
|

Ether Lipids in Obesity: From Cells to Population Studies

Abstract: Ether lipids are a unique class of glycero- and glycerophospho-lipid that carry an ether or vinyl ether linked fatty alcohol at the sn-1 position of the glycerol backbone. These specialised lipids are important endogenous anti-oxidants with additional roles in regulating membrane fluidity and dynamics, intracellular signalling, immunomodulation and cholesterol metabolism. Lipidomic profiling of human population cohorts has identified new associations between reduced circulatory plasmalogen levels, an abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…In addition to conventional LPC with a fatty acyl chain at the sn -1 position, levels of LPC-O carrying an ether linked fatty alcohol were also reduced by NEST overexpression. As one of the major lipid components of the cell membrane, ether glycerophospholipids (ether-GPLs) constitute a significant component of subcellular membranes, such as the nucleus, ER, post-Golgi network and mitochondria membranes [ 40 ]. Ether-GPLs are classified into two types, plasmalogen (1-O-alk-1′-enyl-2-acyl-, i.e., “P”) and alkyl-(1-O-alkyl-2-acyl-, i.e., “O”) GPLs, depending on the substituents at the sn -1 position [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to conventional LPC with a fatty acyl chain at the sn -1 position, levels of LPC-O carrying an ether linked fatty alcohol were also reduced by NEST overexpression. As one of the major lipid components of the cell membrane, ether glycerophospholipids (ether-GPLs) constitute a significant component of subcellular membranes, such as the nucleus, ER, post-Golgi network and mitochondria membranes [ 40 ]. Ether-GPLs are classified into two types, plasmalogen (1-O-alk-1′-enyl-2-acyl-, i.e., “P”) and alkyl-(1-O-alkyl-2-acyl-, i.e., “O”) GPLs, depending on the substituents at the sn -1 position [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ether-GPLs are classified into two types, plasmalogen (1-O-alk-1′-enyl-2-acyl-, i.e., “P”) and alkyl-(1-O-alkyl-2-acyl-, i.e., “O”) GPLs, depending on the substituents at the sn -1 position [ 41 ]. Ether-GPLs have different physical properties from diacyl-GPLs and have been detected at high levels in brain cells [ 39 , 40 ]. Levels of LPC-O were demonstrated to be associated with the onset and progression of Alzheimer’s disease in mice [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to abundant levels of PUFAs at the sn-2 position, plasmalogens are also considered key storage depots of PUFAs. These PUFAs can be cleaved and metabolized into potent second messenger molecules, such as protectins and resolvins, to induce anti-inflammatory and anti-apoptotic effects ( 103 ). Whether increasing the level of plasmalogens in β cells can protect pancreatic β cells from oxidative damage requires further investigation.…”
Section: Effects Of Lipids On T1dmmentioning
confidence: 99%
“…101 While cognitive aging and neurodegenerative diseases such as AD have emerged as a brain or CNS manifestation of metabolic diseases, 102 recent studies in large human cohorts revealed reduced circulating levels of Pls in metabolic diseases, including obesity, hypertension, pre-diabetes, type 2 diabetes, and non-alcoholic fatty liver disease. 103 Among the underlying mechanisms, multiple pathways were pointed out, including the disruption of cellular and mitochondrial membranes, increased oxidative stress, ER dysfunction, and inflammation. 103 Changes in cellular metabolism, from the highly efficient oxidative phosphorylation (taking place in mitochondria) to glycolysis (in cytosol), notably occurring when mitochondrial structure and function is compromised, 85,86,104 were also linked to microglial dysfunction and reactivity, together with impaired synaptic plasticity and cognitive aging in mice.…”
Section: Lowered Pls Levels In Neurodegenerative Inflammatory and Met...mentioning
confidence: 99%
“…103 Among the underlying mechanisms, multiple pathways were pointed out, including the disruption of cellular and mitochondrial membranes, increased oxidative stress, ER dysfunction, and inflammation. 103 Changes in cellular metabolism, from the highly efficient oxidative phosphorylation (taking place in mitochondria) to glycolysis (in cytosol), notably occurring when mitochondrial structure and function is compromised, 85,86,104 were also linked to microglial dysfunction and reactivity, together with impaired synaptic plasticity and cognitive aging in mice. 105 Furthermore, in the inherited metabolic disorder, Barth syndrome, impaired levels and molecular properties of the mitochondrial-specific lipids cardiolipins were measured.…”
Section: Lowered Pls Levels In Neurodegenerative Inflammatory and Met...mentioning
confidence: 99%